Effect of non-essential amino acids (proline and glutamic acid) and sugar polyol (sorbitol) on brood of honey bees - Noor-ul-Ane, Muhammad; Jung, Chuleui (Frontiers in Ecology and Evolution, 2022)
Dietary nutrients provide fuel for growth and development and also required chemicals which are used for tissue constructions of insects. Apis mellifera L., an important pollinator, collects nectar and pollens from different plants to get their nutritional needs. Honey bees use protein for growth and development and carbohydrates as energy sources. Pollens predominantly contain proline and glutamic acid (non-essential amino acids). This is the first study to evaluate the role of proline and glutamic acid on bee brood. Optimization of In Vitro rearing can be achieved by diet composition. Therefore, we elaborated on the possible impact of these amino acids and sugar alcohol on bee brood. To achieve this objective, honey bee larvae were reared on different concentrations of proline, glutamic acid and sorbitol (1, 4 and 8%) which were supplemented into the standard larval diet. The supplementation of proline helped quick development of larvae and pupae of honey bees. But developmental time only decreased in pupae in case of glutamic acid. The total bee brood development duration was shortest (20.1 and 20.6 days) on Pro8 and Glu4, respectively. Proline only increased larvae survival (93.8%) whereas glutamic acid did not increase the survival of any brood stage. Pupal and adult weights were also increased with proline and glutamic acid supplemented diets. Sorbitol did not change the developmental period of honey bee brood but increased larval survival (93.7%) only at lowest concentration (Sor1). Higher concentration (Sor8) of sorbitol reduced the body weight of both pupae and adults. This study predicts that bee brood raising could be one of the factors for selectivity of pollen with higher proline and glutamic acid during bee’s foraging. The small concentration of sorbitol can be used to increase the survival of honey bee brood.